The Effect of Problem-Based Learning Model with Learning Videos on Learning Motivation, Critical Thinking Ability, and Social Studies Learning Outcomes - Fitriani, Nurul; Babo, Rosleny; Nawr, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
The purpose of this research is to ascertain how Problem-Based Learning (PBL), with the use of instructional videos, affects students' learning achievement in Social Studies (IPS) classes at Gugus I Panakkukang District Elementary School in Makassar City, as well as their learning motivation and critical thinking abilities. This research employed a non-equivalent control group design in a quasi-experimental setup. There were 27 students in the experimental group and 29 in the control group out of the total 56 students in the sample. Tests of academic accomplishment and critical thinking skills, learning motivation surveys, observation, and recordkeeping were some techniques used to gather data. Descriptive statistical methods, inferential analysis, and MANOVA hypothesis testing were used to investigate the data. The results demonstrated that: 1) PBL with learning videos substantially impacted students' learning motivation (p = 0.000 < 0.05);. It is anticipated that the consequences of this research will assist educators in selecting appropriate learning model applications to enhance student learning outcomes.